Effect of tillage, subsidiary crops and fertilisation on plant‐parasitic nematodes in a range of agro‐environmental conditions within Europe. (4th October 2017) - Schmidt, J.H.; Bergkvist, G.; Campiglia, E.; Radicetti, E.; Wittwer, R.A.; Finckh, M.R.; Hallmann, J.
Abstract : The effects of tillage on plant‐parasitic nematodes were generally minor, although no tillage in Italy supported higher densities of Pratylenchus (184 nematodes per 100 ml soil) than inversion tillage (59 nematodes per 100 ml soil). Pratylenchus densities were 160 nematodes per 100 ml soil when leguminous subsidiary crops were grown, 122 nematodes per 100 ml soil in the green fallow, and 84 nematodes per 100 ml soil after growing black oat (Avena strigosa) or oilseed radish (Raphanus sativus). Crop rotations including specific subsidiary crops are therefore prominent factors affecting indigenous nematode communities, while tillage and fertilizer are of lower importance. Abstract: The overall goal in nematode management is to develop sustainable systems where nematode populations are kept under the economic damage threshold. Conservation tillage and subsidiary crops, applied as cover crops and living mulches, generally improve soil health by increasing soil organic matter content and stimulating soil microbial activity. However, more permanent crop and weed cover associated with subsidiary crops and noninversion tillage, respectively, may benefit plant‐parasitic nematodes with broad host spectra such as Meloidogyne and Pratylenchus . These genera are major constraints to many field crops throughout Europe and there is a need to identify effective and reliable management options that can be applied to avoid excessive infestations. The dynamics of the indigenous fauna of plant‐parasitic nematodes were studied in eight coordinated multi‐environment field experiments (MEEs) under four agro‐environmental conditions in Europe (Continental, Nemoral, Atlantic North and Mediterranean North). The MEEs consisted of a 2‐year sequence of wheat combined with a living mulch or subsequent cover crops and second main crops maize, potatoes or tomatoes depending on site. Additionally, the effects of inversion tillage using the plough were compared with various forms of conservation tillage (no‐tillage, shallow and deep noninversion tillage). Overall, Helicotylenchus, Paratylenchus, Pratylenchus and Tylenchorhynchus were the most frequent genera across sites while Meloidogyne occurred only in Germany at very low densities. During the wheat–maize sequences in Switzerland, the populations of Pratylenchus increased from 63 to 146 nematodes per 100 mL soil and Helicotylenchus from 233 to 632 nematodes per 100 mL soil. The effects of tillage on plant‐parasitic nematodes were generally minor, although no tillage in Italy supported higher densities of Pratylenchus (184 nematodes per 100 mL soil) than inversion tillage (59 nematodes per 100 mL soil). Furthermore, Pratylenchus densities were 160 nematodes per 100 mL soil when leguminous subsidiary crops were grown, 122 nematodes per 100 mL soil in the green fallow and 84 nematodes per 100 mL soil after growing black oat ( Avena strigosa ) or oilseed radish ( Raphanus sativus ). The differences were greatest in Italy, in a sandy soil with low organic matter. Application of compost or nitrogen fertiliser had no consistent effects on plant‐parasitic nematodes. We conclude that crop rotations including specific subsidiary crops are prominent factors affecting the indigenous nematode community, while tillage and fertiliser are of lower importance.